PENGARUH RETURN ON ASSETS (ROA), EARNING PER SHARE (EPS), DAN NET PROFIT MARGIN (NPM) TERHADAP HARGA SAHAM PADA PERUSAHAAN TEKSTIL DAN GARMENT YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2017-2020 - Rahayu, Umi; Triyanto, Eko (Jurnal Kelola: Jurnal Ilmu Sosial, 2022)
The purpose of this study is to examine whether EPS, ROA, and NPM affect stock prices. The study population included 21, the sample used the purposeful sampling method. The data obtained are secondary data from the IDX. at www.idx.co.id. The data analysis technique in this study adopts the multiple linear region analysis technique. The results show that ROA has no significant effect on stock price. Earnings per share have a negative and significant impact on stock prices. Meanwhile, the NPM variable has no significant effect on stock price. Meanwhile, EPS, ROA, and NPM have a significant impact on stock prices. The purpose of this research is to test whether there is an effect of EPS, ROA, and NPM on stock prices.